A Study of Marriage Rites in the Roman, Chaldean and Indian Traditions - Kochappilly, Paulachan (Asian Horizons, 2011)
Arokiaraj Savarimuthu, A Study of Marriage Rites in the Roman, Chaldean and Indian Traditions, Bangalore: Asian Trading Corporation, 2007. Pages: xxii+450. ISBN 8170864216